Enhancing Islamic Economic Literacy through Dhuafa Mart: Community-Based Empowerment for Local Communities - Muhammad Syaipudin; Mifta Hasda; Hidayat Hidayat; Mohd Winario (Journal of Community Service and Empowerment, 2025)
Islamic economic literacy is an important factor in supporting the development of the Islamic economy at the community level. However, public understanding of Islamic economic concepts and practices remains limited, particularly among local communities directly involved in economic activities. This community service program aimed to enhance Islamic economic literacy by strengthening the role of Dhuafa Mart Air Tiris Kampar as a medium for education and community empowerment. The program employed needs identification, presentations, interactive discussions, question-and-answer sessions, and practical examples of implementing Islamic economic principles in daily business activities. The materials covered the contribution of Dhuafa Mart in promoting Islamic economics, Islamic principles of wealth acquisition, consumption and distribution, the application of business ethics based on Hadith, and Islamic financial planning. The results indicated that participants, consisting of Dhuafa Mart managers and employees, actively engaged in the program and demonstrated improved understanding of Islamic economic principles and their application in business management. Furthermore, the program strengthened the role of Dhuafa Mart as an educational platform capable of promoting Islamic economic values in a practical and sustainable manner. Therefore, this initiative contributes to improving